TRADISI NGUTANG DI PASAR TRADISIONAL (Studi di Pasar Tradisional Gunungpati) - Baidhowi, Baidhowi (Sabda: Jurnal Kajian Kebudayaan, 2015)
The traditional market is an important place in the life of the Java community. For society, the market not only as a meeting place for sellers and buyers, but also as a forum for social interaction and representation of traditional values indicated by market actors (traders, buyers and banks thithil / renten). The actors in offering their goods prioritizing personal approach and familial / social networking. Established market atmosphere is not just a formal relationship of buying and selling between sellers and buyers, but more than that, that they greet each other and chat. So for the people shopping at a crowded market and not too clean it into the enjoyment of life of its own. Capital constraints for traders to be one of a phenomenon that is addressed to "ngutang". On the other hand not a few traders in traditional markets by way of its trading strategy are debted. What is interesting how the tradition owe both by traders and buyers as well to whom they debt.This is Qualitative research with phenomenological approach. Collect data with interview techniques. The results showed that the tradition of debt for the traditional market actors Gunungpati done with some motive or model. First group owe a shopper to traders in the market. In this group, in fact the buyer does not merely want to owe. Debt settlement, the traders wait for repayment by the buyer. The second group, the debt carried by traders to moneylenders / bank thithil. Capital constraints often encourage traders to seek additional capital. Their interest in debt to loan sharks, although the excess returns occur because of several motives, among other things, increase business capital, join friends / tempted by the offer attractive, need urgent funds for other purposes. While the model of the solution is the moneylenders who seized merchandise, no patient by giving time. Instead models of debt repayment by merchants a variety of characters, there is the discipline to pay any bank thithil paramedics came. There are â€œendoâ€/ evoid with unsold merchandise reason. Finally been booked to trust banks thithil real customers also remedy immediately pay off, not rare bicker.